-3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11

Simple and best practice solution for -3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+5+(-4x+6)+7x=(2.4x-3.7)(-3)-7.2x+11 equation:


Simplifying
-3x + 5 + (-4x + 6) + 7x = (2.4x + -3.7)(-3) + -7.2x + 11

Reorder the terms:
-3x + 5 + (6 + -4x) + 7x = (2.4x + -3.7)(-3) + -7.2x + 11

Remove parenthesis around (6 + -4x)
-3x + 5 + 6 + -4x + 7x = (2.4x + -3.7)(-3) + -7.2x + 11

Reorder the terms:
5 + 6 + -3x + -4x + 7x = (2.4x + -3.7)(-3) + -7.2x + 11

Combine like terms: 5 + 6 = 11
11 + -3x + -4x + 7x = (2.4x + -3.7)(-3) + -7.2x + 11

Combine like terms: -3x + -4x = -7x
11 + -7x + 7x = (2.4x + -3.7)(-3) + -7.2x + 11

Combine like terms: -7x + 7x = 0
11 + 0 = (2.4x + -3.7)(-3) + -7.2x + 11
11 = (2.4x + -3.7)(-3) + -7.2x + 11

Reorder the terms:
11 = (-3.7 + 2.4x)(-3) + -7.2x + 11

Reorder the terms for easier multiplication:
11 = -3(-3.7 + 2.4x) + -7.2x + 11
11 = (-3.7 * -3 + 2.4x * -3) + -7.2x + 11
11 = (11.1 + -7.2x) + -7.2x + 11

Reorder the terms:
11 = 11.1 + 11 + -7.2x + -7.2x

Combine like terms: 11.1 + 11 = 22.1
11 = 22.1 + -7.2x + -7.2x

Combine like terms: -7.2x + -7.2x = -14.4x
11 = 22.1 + -14.4x

Solving
11 = 22.1 + -14.4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14.4x' to each side of the equation.
11 + 14.4x = 22.1 + -14.4x + 14.4x

Combine like terms: -14.4x + 14.4x = 0.0
11 + 14.4x = 22.1 + 0.0
11 + 14.4x = 22.1

Add '-11' to each side of the equation.
11 + -11 + 14.4x = 22.1 + -11

Combine like terms: 11 + -11 = 0
0 + 14.4x = 22.1 + -11
14.4x = 22.1 + -11

Combine like terms: 22.1 + -11 = 11.1
14.4x = 11.1

Divide each side by '14.4'.
x = 0.7708333333

Simplifying
x = 0.7708333333

See similar equations:

| 2/5=x/25 | | 2(3x+1)+x-3(2x+1)=x+4(x-1)-(4x+3) | | -1(3x+4)-4x=-2(4x-3)+2 | | 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k | | 2x^8-4x^7+10x^6=0 | | x/48=6/12 | | 3x+3(x+2)=6 | | 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 | | 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 |

Equations solver categories